Comparison of lea gratings with cardiff acuity cards for vision testing of preverbal children - Mody, Kruti H (Medknow Publications & Media Pvt Ltd, 2012)
AIMS: To create a normative data for lea grating (LG) in the Indian population and to compare LG with Cardiff Acuity Card (CAC). SETTINGS AND DESIGN: Normative Data was acquired from normal children between 6 months-3 years coming to the ‘Immunisation Clinic’ and ‘Well-Baby Clinic’ at a Civil Hospital. To compare LG with CAC, normal and amblyopic children between 6 months-3 years were evaluated, MATERIALS AND METHODS: Monocular and binocular visual acuity (VA) was measured using LG and then CAC. VA and time taken to perform the test were compared. STATISTICAL ANALYSIS USED: Pearson's Correlation Coefficient to compare VA and Student paired t-test (significance P<0.005) to compare time. RESULTS: Two standard deviations of VA of 100 normal children overlapped with that published by Lea. Of the 30 amblyopic children aged 18.32 ± 10.5 months (2-36), 18 were females. VA was 0.95 ± 0.3 logMAR (0.7–1.2) and 1.0 ± 0.6 logMAR (0.5–2.1) binocularly and 1.32 ± 0.08 logMAR (0.2-0.6) and 1.15 ± 0.15 logMAR (0.88-1.48) monocularly on CAC and LG respectively. Pearson's correlation coefficient was 0.98 and 0.63 for binocular and monocular assessment respectively. Time taken to perform LG monocularly and binocularly was significantly less (P<0.001) than CAC. CONCLUSION: Normative data acquired in Indian pre-verbal children is similar to that published by Lea. Though VA by CAC is better than LG, the two tests are comparable.